Stearoyl-CoA Desaturase-1 Attenuates the High Shear Force Damage Effect on Human MG63 Osteosarcoma Cells - Kuo-Chin Huang (International Journal of Molecular Sciences, 2020)
Mechanical regulation is known as an important regulator in cancer progression and malignancy. High shear force has been found to inhibit the cell cycle progression and result in cell death in various cancer cells. Stearoyl-CoA desaturase (SCD)-1, one of the important lipogenic enzymes, has recently been indicated as a potential pharmaceutical target in cancer therapy. In this study, we determined whether the cell fate control of shear force stimulation is through regulating the SCD-1 expression in cancer cells. Human MG63 osteosarcoma cells were used in this study. 2 and 20 dynes/cm2 shear forces were defined as low and high intensities, respectively. A SCD-1 upregulation in human MG63 osteosarcoma cells under 20, but not 2, dynes/cm2 shear force stimulation was shown, and this induction was regulated by Smad1/5 and peroxisome proliferator-activated receptor δ (PPARδ) signaling. Moreover, gene knockdown of PPARδ and SCD-1 in human MG63 osteosarcoma cells attenuated the differentiation inhibition and resulted in much more cell death of high shear force initiation. The present study finds a possible auto-protective role of SCD-1 upregulation in high shear force-damaged human MG63 osteosarcoma cells. However, its detailed regulation in the cancer fate decision of high shear force should be further examined.